Biology of plants - Raven, Peter H. (W.H. Freeman, 2003)
This introduction to botany has been revised and completely reorganized - from the molecular and cellular through the whole organism to the ecosystem. The authors emphasize the relationships between growth and development, and structure and function, within the all-pervading themes of evolution and ecology. Features of the 6th editon include: coverage of diversity informed by recent sequencing studies and cladistic analyses; inclusion of current advances due to molecular techniques and biotechnology; and new material on ethnobotany and medicinal plants